Acromegaloid Facial Appearance: Case Report and Literature Review - Adline Ghazi; Shikha Khosla; Kenneth Becker (Case Reports in Endocrinology)
Pseudoacromegaly is characterized by an acromegalic appearance without any abnormality of growth hormone function. It may be caused by several congenital and acquired conditions. One such condition is the acromegaloid facial appearance (AFA) syndrome. This condition has been described in approximately eight cases/families. It encompasses a spectrum of acromegaloid physical findings, normal growth hormone (GH) and insulin-like growth factor one (IGF-1) levels, and variable mode of inheritance. The most common physical findings are coarse facies, bulbous nose, and thickened lips. We present a case and a review of the literature on this illness. The patient is a 57-year-old woman who was referred to the endocrinology division for evaluation of suspected acromegaly. She had an acromegaloid appearance since birth as well as a terminal hypertrichosis. Her endocrine laboratory evaluation and chromosomal analyses were normal. AFA needs to be considered when evaluating any patient with pseudoacromegaly. Additional cases/families need to be identified in order to better understand the clinical spectrum, clinical implications, and mode of inheritance of AFA.